Fundamentals of Necklift - Viterbo, Fausto [UNESP]; Neto, Balduíno [UNESP]; Magnani, Lucas [UNESP] (Springer Nature, 2024)
The neck complements the facial contour and when it is well outlined it is associated with youthfulness and an attractive appearance. Knowing its anatomical particularities and the aging process that each structure presents is essential to treat it properly. In many cases, neck lift treatment is independent of a facelift and can bring transformative results. However, most of the time, treating the pre-platysmal fat exclusively, for example, is not enough and can bring results that are difficult to revise. At the end of this chapter, the surgeon should understand how essential it is to identify the structures that need to be corrected, as well as to approach them appropriately.